Analysis of the Accuracy of Writing Simple Stories Assisted by Picture Series Media in Elementary School - Fatmi Rohmah Nur Hidayati; Markhamah; Fitri Puji Rahmawati (Elementary Teacher Education Program, Majalengka University, 2024)
This study aims to describe the effectiveness of Indonesian language learning in writing simple stories with serial picture media. This simple story writing skill has indicators that include: the suitability of simple stories and writing simple stories. The type of research conducted is descriptive qualitative with data in the form of simple stories as the basic material for study and analysis. The data in this study are simple story writing of students in class II SDIT Muhammadiyah Al-Kautsar. The data sources in this study were 20 students, the techniques used in the research were simple story writing test techniques. Data collection in the study through the task of writing a simple story with serial image media. The results of research at SDIT Muhammadiyah Al-Kautsar related to simple story writing skills, namely, students in writing simple stories using serial image media can follow well so that students are able to compile simple stories by understanding the indicators in writing skills coherently. In addition, students are very enthusiastic in using serial image media as a solution in compiling and writing simple stories. However, in the writing accuracy indicator, students have not been precise in writing simple stories.